Online Education and Reproduction of Educational Inequalities: Schooling Practices in India during Corona Pandemic - Rathee, Sharmila (Indian Journal of Educational Technology, 2022)
In India, efforts to make educational systems accessible and inclusive of the needs of students were still in progress, when an unprecedented situation caused by the Corona virus pandemic 2019 (Covid-19) radically changed the landscape and functioning of the schools all across the country. With schools shifting completely to online mode during the pandemic times, students belonging to disadvantaged groups got placed at risk of missing educational opportunities. The present paper attempts to study the nature of educational practices in an elite private school in the capital city, Delhi, India at the time of nationwide physical school closures due to Covid-19. Using quantitative and qualitative methods, findings from this study suggest that the online mode of education is causing several challenges related to access and participation. Using Pierre Bourdieu’s key concepts of field, capital and habitus, findings from the field have been analyzed in light of the theoretical framework of reproduction of inequalities in education.